2021
DOI: 10.17582/journal.aavs/2021/9.7.1045.1052
|View full text |Cite
|
Sign up to set email alerts
|

In vivo -Cellular and Humoral Immune Response for Evaluation of Propolis Effect on Chronic Toxoplasmosis in Rats

Abstract: T oxoplasma gondii (T. gondii) is a pathogenic protozoan affecting humans and animals causing toxoplasmosis disease (Dubey, 2008). Infection with T. gondii may cause abortion, stillbirth, and neonatal death in human (Innes, 2010) and in animals (Tenter et al., 2000). About one-third of the human populations worldwide are infected with T. gondii (McConkey et al., 2013). Barakat et al. (2018) stated that seropositive aborted women were 50.7% by ELISA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
3
6
0
Order By: Relevance
“…According to our findings, propolis can significantly reduce the parasite load in the examined organs, revealing that the stained tissue smears (liver) obtained from the animals treated with propolis exhibited a significant reduction in the parasite load compared to the positive control group. This result agrees with a previous work [ 51 ] that reported that propolis extract alone can reduce the average brain parasite load during chronic toxoplasmosis by 16.71%. Furthermore, in the same study [ 51 ], the propolis extract achieved a higher reduction percentage (31.74%) when combined with spiramycin, potentiating the therapeutic activity of spiramycin.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…According to our findings, propolis can significantly reduce the parasite load in the examined organs, revealing that the stained tissue smears (liver) obtained from the animals treated with propolis exhibited a significant reduction in the parasite load compared to the positive control group. This result agrees with a previous work [ 51 ] that reported that propolis extract alone can reduce the average brain parasite load during chronic toxoplasmosis by 16.71%. Furthermore, in the same study [ 51 ], the propolis extract achieved a higher reduction percentage (31.74%) when combined with spiramycin, potentiating the therapeutic activity of spiramycin.…”
Section: Discussionsupporting
confidence: 94%
“…This result agrees with a previous work [ 51 ] that reported that propolis extract alone can reduce the average brain parasite load during chronic toxoplasmosis by 16.71%. Furthermore, in the same study [ 51 ], the propolis extract achieved a higher reduction percentage (31.74%) when combined with spiramycin, potentiating the therapeutic activity of spiramycin. One more study proved the antiprotozoal activity of propolis since it inhibits tachyzoite multiplication, and its antiparasitic effect could be related to the presence of caffeic acids, terpenoids, and flavonoids [ 33 ].…”
Section: Discussionsupporting
confidence: 94%
“…Six weeks post-infection, herbal ingredients were orally administered to mice daily using a stomach tube for 10 days [ 44 ]. The mice were divided into the following five groups (10 mice per group): Group 1 (G1), negative control: noninfected, nontreated mice; Group 2 (G2), positive control: infected, nontreated mice; Group 3 (G3): infected and treated with 0.1 mL propolis extract/day [ 45 ]; Group 4 (G4): infected and treated with WGO at a dose of 0.2 mg/1.5 mL/per kg body weight/day [ 46 ]; and Group 5 (G5): infected and treated with a combination of WGO and propolis using the same dose in G3 and G4. Mice were assessed daily for any clinical signs.…”
Section: Methodsmentioning
confidence: 99%
“…Noticeably, IFN-γ sera levels were increased following the Toxoplasma infection (subgroup IIa). Our results were in accordance with Gaafar et al ., [ 10 ] and Hegazi et al ., [ 63 ] who reported that a strong cellular immune response was elicited by high IFN-γ production during acute and chronic toxoplasmosis, respectively. Although, the IFN-γ production is apparently blocked in the infected cells, rapid growth of the T .…”
Section: Discussionmentioning
confidence: 99%